I have been working on a proof which involves sums and products going to infinity. I am wondering whether the following proof of a limit is valid, and whether that result would allow me to come to another conclusion.

What is:

$$\lim \limits_{n \to \infty} f(n)\text {, where }f(n) = n-n$$

I have worked this out to be

$$\lim \limits_{n \to \infty} n-n = \lim \limits_{n \to \infty} n(1-1) = \lim \limits_{n \to \infty} n\cdot 0 = 0$$

I'm not sure whether this is the correct way of proving this limit, or whether the answer is correct. My math teacher had said that the whole limit raised a red flag in his mind, and he wasn't sure why.

If my limit is correct, though, I would like to know whether the following is also valid:

$$\lim \limits_{n \to \infty} f(n)\cdot n = 0$$

  • 13
    $\begingroup$ The red flag might be that $x_n\to\infty$ and $y_n\to0$ implies nothing about the asymptotics of $x_ny_n$. But here $f(n)=0$ for every $n$ hence $x_nf(n)=0$ for every $n$ hence $x_nf(n)\to0$ for every sequence $(x_n)$ (and to tell you the truth, this makes for a rather bizarre question). $\endgroup$
    – Did
    Dec 17, 2016 at 21:37
  • 6
    $\begingroup$ It's easier than that. f(n) = n-n = 0 is a constant function. $\endgroup$
    – fleablood
    Dec 18, 2016 at 2:37
  • 4
    $\begingroup$ $\lim n*0$ is ambiguous. It could mean $\lim (n*0)$ which is no easier or harder to solve than $\lim (n-n)$ or it could mean $(\lim n)*0$ which may not be a valid conclusion and may not be 0. BTW why do you think $\lim n*0 = 0$? $\endgroup$
    – fleablood
    Dec 18, 2016 at 2:41
  • 4
    $\begingroup$ $f(n)=n-n$ is just a roundabout way to say $f(n)=0\,$, so $\lim_{n \to \infty} f(n) = \lim_{n \to \infty} 0 = 0$. This should not be confused, however, with $\lim_{n \to \infty} (n-n) = \lim_{n \to \infty} n - \lim_{n \to \infty} n$ which is wrong and undefined. $\endgroup$
    – dxiv
    Dec 18, 2016 at 3:42
  • $\begingroup$ @dxiv AFAIK $\lim_{n \to \infty}{n-n}=0$. It's not completely clear from your comment that the error is in "splitting the limit". You can "split the limit" only: 1) when they are factors and 2) the individual limits exist and are finite (e.g. $\lim_{x \to \infty}{f(x) \cdot g(x)} = (\lim_{x \to \infty}{f(x)})\cdot(\lim_{x \to \infty}{g(x)})$ provided these last two limits exist and are finite). $\endgroup$
    – Bakuriu
    Dec 18, 2016 at 9:15

3 Answers 3


If $f(n) = n-n$, then $f(n) = 0$ for all $n$. The limit you gave is true, i.e. $$\lim\limits_{n\to \infty} f(n) = 0$$ is correct.

Furthermore, we have that $n\cdot f(n) = n\cdot 0 = 0$ for all $n$, so the limit $$\lim\limits_{n\to\infty}n\cdot f(n) = 0$$ is also correct.

The red flag probably stems from the well known "indeterminate form" $\infty -\infty$. This is short hand notation for the fact that knowing $$\lim\limits_{n\to \infty} g(n) = \infty\quad\text{ and }\quad \lim\limits_{n\to\infty} h(n) = \infty $$ is not enough by itself to determine $$\lim\limits_{n\to\infty}(g(n)-h(n)).$$ Similarly, $\infty\cdot 0$ is also an indeterminate form, i.e. knowing $$\lim\limits_{n\to \infty} g(n) = \infty\quad\text{ and }\quad \lim\limits_{n\to\infty} h(n) = 0$$ is not enough to determine $$\lim\limits_{n\to\infty} g(n)\cdot h(n).$$


Yes this is correct. If you define $f(n)=n-n$ it is sufficient to notice that $f(n) \equiv 0$


When in doubt you can always go back to the definition of a limit. If $\lim_{n\to\infty} f(n)$ is going to have a value, $L$, it means that for any positive "deviation" $\epsilon$, no matter how small, there is a range $[N,\infty)$ such that, throughout that entire range, $f(n)$ never gets further away from $L$ than $\epsilon$.

In this case, $f(n) = 0$ for all $n$. So if we pick $L = 0$, then no matter what $\epsilon$ you pick, $f(n)$ is always that close to $L$ because it's exactly equal to $L$ everywhere. This reasoning also shows you that, for any function of a real number which always takes the same value (a constant function), its limit at any point or at $\pm\infty$ is equal to that value.

This is, of course, the "nontechnical" way to phrase it, but the idea is the same if you do a proper proof.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.